Chronic kidney disease as a risk factor for peripheral nerve impairment in older adults: A longitudinal analysis of Health, Aging and Body Composition (Health ABC) study. - Simit Doshi (Public Library of Science (PLoS), 2020)
Introduction Sensory and motor nerve deficits are prevalent in older adults and are associated with loss of functional independence. We hypothesize that chronic kidney disease predisposes to worsening sensorimotor nerve function over time. Materials and methods Participants were from the Health, Aging and Body Composition Study (N = 1121) with longitudinal data between 2000-01 (initial visit) and 2007-08 (follow-up visit). Only participants with non-impaired nerve function at the initial visit were included. The predictor was presence of CKD (estimated GFR ≤ 60 ml/min/1.73m2) from the 1999-2000 visit. Peripheral nerve function outcomes at 7-year follow-up were 1) Motor: "new" impairments in motor parameters (nerve conduction velocity NCV < 40 m/s or peroneal compound motor action potential < 1 mv) at follow-up, and 2) Sensory: "new" impairment defined as insensitivity to standard 10-g monofilament or light 1.4-g monofilament at the great toe and "worsening" as a change from light to standard touch insensitivity over time. The association between CKD and "new" or "worsening" peripheral nerve impairment was studied using logistic regression. Results The study population was 45.9% male, 34.3% Black and median age 75 y. CKD participants (15.6%) were older, more hypertensive, higher in BMI and had 2.37 (95% CI 1.30-4.34) fold higher adjusted odds of developing new motor nerve impairments in NCV. CKD was associated with a 2.02 (95% CI 1.01-4.03) fold higher odds of worsening monofilament insensitivity. CKD was not associated with development of new monofilament insensitivity. Conclusions Pre-existing CKD leads to new and worsening sensorimotor nerve impairments over a 7-year time period in community-dwelling older adults.